Pertumbuhan Bakteri Bacillus Subtilis Pada Media Biji Nangka Dan Biji Kluwih Sebagai Substitusi Media Na (Nutrient Agar) - LESTARI, DEWI PUTRI YUNI, Triastuti Rahayu, S. Si, M. Si (2016)
ABSTRACT Dewi Putri Yuni Lestari/A420120046. THE GROWTH OF BACTERIA Bacillus subtilis IN THE MEDIA Artocarpus heterophyllus SEEDS AND Artocarpus communis SEEDS AS A SUBSTITUTION MEDIA OF NA (NUTRIENT AGAR). Skripsi. School of Teacher Training and Education. Muhammadiyah University of Surakarta. March, 2016 The microbial cultured media required a high costed and therefore researchers want to create alternative media used cheap local raw materials from Artocarpus heterophyllus seeds and artocarpus communis seed. This study aimed to determine the growth of Bacillus subtilis in the media Artocarpus heterophyllus seeds and grains as a substitute Artocarpus communis seeds NA media. This study used a completely randomized design (CRD) with one treatment factors are the type of media Artocarpus communis seeds, Artocarpus heterophyllus seeds and seeds of each treatment with three replications. Inoculated with the test bacteria spread plate method and incubated at 37 ° C for 24 hours. The parameters were measured the number of population and the size of the bacterial colonies. The highest population in the media from the seeds of media Artocarpus heterophyllus seeds(5.92 x 107 CFU / ml), media Artocarpus communis seed (2.77 x 107 CFU / ml), then the last media Nutrient Agar (2 x 107 CFU / ml). Based on size of bacterial colonies, from the second seed medium gets the smaller size than NA media but its population is more in seed media. The conclusion of this research is the growth of Bacillus subtilis in the media Artocarpus heterophyllus seeds and grains as a substitute Artocarpus communis can be used as substition media of Nutrient Agar. Keywords: Artocarpus heterophyllus, Arocarpus communis, and bacterial growth media.